Go with the flow - menstrual health experiences of athletes and coaches in Scottish swimming - Zipp, Sarah; Hyde, Molly (Sport in society, 2024)
Menstruation is widely considered a taboo subject, one that is not openly discussed and is often misunderstood. Although recent social movements have created more public awareness, there is still a lack of research and advocacy on menstrual health in sport. This study aims to contribute new knowledge on this important topic, including its impact on athletes, its role in coach education and on strategies for supporting athletes. In collaboration with Scottish Swimming, our study included semi-structured interviews with 13 coaches and 6 athletes. Both coaches and athletes felt they lacked knowledge and expressed a strong desire for menstrual health education in sport. Notably, most coaches were not confident that their knowledge would enable them to offer practical advice. Athletes indicated an openness about discussing the menstrual cycle, especially as they got older. We conclude that menstrual health education should be formally incorporated into coaching education, which will improve athlete experience.